171: TOTAL VERSUS SUBTOTAL GASTRECTOMY FOR DISTAL GASTRIC POORLY COHESIVE CARCINOMA. (23rd April 2022) - Boubaddi, M; Lambert, C; Piessen, G; Gualtierotti, M; Voron, T; Mantziari, S; Ferrari, G; Pezet, D; Gronnier, C
Abstract: Background and aim: Gastric poorly cohesive carcinoma (PCC) is characterized by a submucosal diffusion, an early lymph node and peritoneal extension associated with a worth prognosis for locally advanced stage (T2-T4) than intestinal type of adenocarcinoma. Total gastrectomy (TG) is still the most frequent procedure realized for distal gastric PCC because of its invasive characteristics. However, subtotal gastrectomy (SG) for antro-pyloric localization could improve morbidity and quality of life without compromising oncological outcomes. At this day, there is no clear recommendation about the type of surgery to realize for distal PCC gastric cancer. The aim of this study was to compare overall survival (OS) and disease-free survival (DFS) for patients with antro pyloric PCC treated by SG vs those treated by TG. Methods: We use a retrospective European multicentric cohort of 2327 patients treated for gastric cancer between 2007 and 2017 by members of the French Association of Surgery (AFC). Results: All in all, this study included 271 patients with antro pyloric PCC treated by gastrectomy with 131 who underwent SG and 140 patients who underwent TG. Baseline characteristics were globally similar. We didn't observe any significant difference for tumor stage pTNM. The median length of stay for patients with SG was 11 days (8–16) but for TG it was 13 days (10–18) ( P = 0, 001). There was no significant difference on surgical reintervention with 13 patients in each group ( P = 0, 93). Concerning surgical complications, we used Dindo-Clavien classification: 60% of patients with SG had stage I-IIIa complication against 77% for TG and 8.8% had stage IIIB-IVb against 14, 4% ( P < 0.001). There was no significant difference on 5-year overall survival years between SG (53.1% CI95% = 41.5–63.5%) and TG (53.8% CI95% = 43.2–63.3%) (HR = 0, 94 CI95% = 0, 68-1, 29). We also found no significant difference on 5-year disease free survival between SG (45.3% CI 95% = 34.3–55.6%) and TG (46.0% CI 95% = 35.9–55.5%) (HR = 0, 97 CI95% = 0, 69-1, 33). Conclusion: Our results show that there was no significant difference between SG and TG for 5-year OS and DFS for distal PCC with a lower complication rate in SG group. SG seems to be a valuable strategy for distal PCC.